2015
DOI: 10.1097/jto.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-Catenin Enhances the Anticancer Effect of Irreversible EGFR-TKI in EGFR-Mutated Non–small-cell Lung Cancer with a T790M Mutation

Abstract: Our findings indicate that β-Catenin might be a novel therapeutic target in EGFR-mutated NSCLC carrying the T790M mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 48 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…Apart from the oncogenic role of Wnt signaling in cancer metastasis and invasion, dysregulations of Wnt signaling pathways, particularly the canonical Wnt pathway, have been demonstrated to contribute to therapeutic resistances in many cancer types [31, 37, 44, 6972]. In this regard, Wnt5a was also found to modulate cell cycle progression and contributes to the chemoresistance in pancreatic cancer cells [70] and regulates ABCB1 expression in multidrug-resistant breast cancer cells through activation of the noncanonical PKA/beta-catenin pathway [48].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the oncogenic role of Wnt signaling in cancer metastasis and invasion, dysregulations of Wnt signaling pathways, particularly the canonical Wnt pathway, have been demonstrated to contribute to therapeutic resistances in many cancer types [31, 37, 44, 6972]. In this regard, Wnt5a was also found to modulate cell cycle progression and contributes to the chemoresistance in pancreatic cancer cells [70] and regulates ABCB1 expression in multidrug-resistant breast cancer cells through activation of the noncanonical PKA/beta-catenin pathway [48].…”
Section: Discussionmentioning
confidence: 99%
“…The growth-inhibitory effects of drugs were examined using a 3,4,-5-dimethyl-2H-tetrazolium bromide assay (MTT; Sigma-Aldrich) (16). The experiment was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…A western blot analysis was performed as described previously (16). Briefly, subconfluent cells were washed with cold phosphate-buffered saline (PBS) and harvested with lysis A buffer containing 1% Triton X-100, 20 mM Tris-HCl (pH 7.0), 5 mM EDTA, 50 mM sodium chloride, 10 mM sodium pyrophosphate, 50 mM sodium fluoride, 1 mM sodium orthovanadate, and a protease inhibitor mix, Complete™ (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…A large-scale phase III trial (PETACC-8 trial) demonstrated that the BRAF V600E mutation led to shorter disease-free survival and overall survival times in patients with microsatellite-stable colon cancers treated with a combination of leucovorin, fluorouracil and oxaliplatin, with or without cetuximab (29). By contrast, activation of the Wnt/β-catenin pathway led to increased stemness of cancer cells and drug resistance (30)(31)(32)(33). Wnt/β-catenin signaling was constitutively activated in breast cancer stem cells, and blockade of the Wnt/β-catenin pathway inhibited cancer metastasis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Increased nuclear translocation and activation of β-catenin converted CRC cells into cancer stem cells (32). In a non-small-cell lung cancer cell line carrying the EGFR T790M mutation, inhibition of β-catenin activity resulted in inhibition of cancer cell stemness and sensitivity to an irreversible tyrosine kinase inhibitor (33). Taken together, these results indicate that activating BRAF and β-catenin mutations are individual promoters of tumorigenesis and cancer drug resistance, and that the BRAF V600E and CTNNB1 T41A double mutation expands the range of therapeutics that the cancer is resistant to, as well as the complexity and difficulty of developing effective treatments.…”
Section: Discussionmentioning
confidence: 99%